Pest management of rice farmers in Asia - IRRI (IRRI, 1997)
The book has targeted four specific audiences: *) Researchers and extension spesialists in pest management or related fields who direct or are involved in studies of farmers' knowlege attitude, and practices. **) Academics and trainer who prepare others to design and conduct farmer surveys or to use the results. ***) Extension workers who carry out pest management efforts, conduct farmer trainning programa, and design communication material. ****) Agriculture administrators and policymakers who design and implement national or regional policies related to pest management.